(untitled) (Edad Media. Revista de Historia, 2026)
This article offers the first systematic study of the cobijeras who served the kings of Castile in the late Middle Ages. Drawing on legal, literary, and above all documentary sources –most of them unpublished– it analyses their functions, their hierarchical position in relation to ladies-in-waiting and chambermaids, and the role they played within the monarch’s intimate sphere. The trajectories of several of these women are reconstructed, with particular attention to Sancha de Salazar, whose close relationship with John II enabled her to obtain significant royal grants, patrimonial assets, and an advantageous marriage. The study shows how these women, often of modest or converso origin, achieved notable social advancement and established family networks at court. The cobijeras, hitherto virtually ignored by historiography, thus emerge as a key female office within the institutional and domestic dynamics of the late medieval castilian Royal Household.